The Forms of Political Participation in Coastal Communities during the 2020 Mayoral Election in Makassar - Andi Mardaya; Rahmat Muhammad; Suparman Abdullah; Umar Ramli; Lukman Rais (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
This research aims to analyze the forms of political participation of coastal communities in the 2020 Local Election in Makassar City. The research method employed is qualitative and descriptive. The study is conducted in the Sangkarrang Islands Regency, with data collection techniques including observation, in-depth interviews, and document analysis. The research took place from February to March 2023. The selection of informants was done through purposive sampling, involving 6 (six) individuals, including representatives from district and sub-district governments, election organizers such as the Election Commission (KPU) and Election Supervisory Board (Panwaslu), youth leaders, community and religious leaders, as well as women leaders familiar with the political forms and participation of coastal communities. The research findings indicate that the forms of community participation in the Makassar mayoral election are reflected in political socialization, campaigns, voting, and the counting process. During political socialization, participation is notably low due to occupational factors. In political campaigns, some members of the community abstain from campaigning, considering it unproductive and a waste of time, while others view it as a communal endeavor. The voter turnout during the election is high, reaching a percentage of 66.84%. Simultaneously, the vote count also demonstrates significant participation, driven by the desire to assess whether the elected local leaders align with community expectations